PENGEMBANGAN LABORATORIUM VIRTUAL SEBAGAI MEDIA PRAKTIKUM ALTERNATIF PADA MATA PELAJARAN BIOLOGI DI SMA - ATIKAH, CUCU; Achyani, Achyani; Muhfahroyin, Muhfahroyin (Universitas Muhammadiyah Metro, 2023)
This development research aims to produce a product in the form of an Android-based Catalase Enzyme Test V-Lab application which is expected to be used as an alternative practicum medium for Biology subjects in SMA. in Biology subjects that can support practical activities in the learning process. The research was conducted using the RND (Research and Development) method with the ADDIE development model. The results showed that the results of expert validation from 4 aspects obtained scores with